Resiliencia, disposición al cambio, balance trabajo familia en trabajadores (España y Colombia) - García Rubiano, Mónica; Toro, Ronald; Díaz Fúnez, Pedro Antonio (Pontificia Universidad Católica del Perú, 2024)
This research aimed to analyze the positive effect of willingness to change in its three dimensions (individual, group and organizational), on the generation of personal resources in employees and their perceived balance between work and life. The participants were 320 employees from different companies in Colombia and Spain. Sampling was for convenience. The results show the positive effect of the three levels of acceptance of change, both with the generation of new personal resources and with resilience; as well as with the perception of work-family balance. From this can be inferred the importance for organizations of generating policies aimed at promoting the acceptance of change in work teams and at a global level.

Esta investigación tuvo como objetivo analizar el efecto positivo de la disposición al cambio en sus tres dimensiones (individual, grupal, y organizacional), sobre la generación de recursos personales en los empleados y su percepción balance entre el trabajo y su vida. Los participantes fueron 320 empleados de diferentes empresas de Colombia y España. El muestreo fue por conveniencia. Los resultados muestran el efecto positivo de los tres niveles de aceptación del cambio, tanto con la generación de nuevos recursos personales como la resiliencia; como con la percepción de equilibrio trabajo-familia. De ello se infiere la importancia para las organizaciones de generar políticas orientadas a fomentar la aceptación del cambio en los equipos de trabajo y a nivel global.

Cette recherche visait à analyser l’effet positif de la volonté de changement dans ses trois dimensions (individuelle, collective et organisationnelle), dans la génération de ressources personnelles chez les salariés et dans leur perception de la conciliation entre travail et vie personnelle. Les participants étaient 320 employés de différentes entreprises en Colombie et en Espagne. L’échantillonnage était par commodité. Les résultats montrent l’effet positif des trois niveaux d’acceptation du changement, tant dans la génération de nouvelles ressources personnelles que dans la résilience; ainsi que la perception de la conciliation travail-famille. On en déduit l’importance pour les organisations de générer des politiques visant à favoriser l’acceptation du changement dans les équipes de travail et à l’échelle mondiale.

Esta investigação teve como objetivo analisar o efeito positivo da vontade de mudança nas suas três dimensões (individual, grupal e organizacional), na geração de recursos pessoais nos colaboradores e na sua perceção de conciliação entre trabalho e vida pessoal. Os participantes foram 320 funcionários de diferentes empresas da Colômbia e da Espanha. A amostragem foi por conveniência. Os resultados mostram o efeito positivo dos três níveis de aceitação da mudança, tanto na geração de novos recursos pessoais quanto na resiliência; bem como a percepção do equilíbrio trabalho-família. A partir disso, infere-se a importância de as organizações gerarem políticas voltadas para a promoção da aceitação da mudança nas equipes de trabalho e em nível global.
Resilience, willingness to change, work-family balance in workers (Spain and Colombia)
Résilience, volonté de changement, conciliation travail-famille chez les travailleurs (Espagne et Colombie)
Keywords: Resilience; Work-family balance; Organizational change; Willingness to change; Resiliencia; Balance trabajo familia; Cambio organizacional; Disposición al cambio; Résilience; Conciliation travail-famille; Changement organisationnel; Volonté de changer; Resiliência; Equilíbrio trabalho-família; Mudança organizacional; Vontade de mudar; https://purl.org/pe-repo/ocde/ford#5.01.00